'Interfaces' 7 (Interfaces: A Journal of Medieval European Literatures, 2020)
Issue No. 7 is the third open issue of Interfaces: A Journal of Medieval European Literatures. It contains contributions by Henry Ravenhall, Kristian Jensen, and Ana M. Gómez-Bravo.Cover image: Marianne Therese Grønnow, Light. Dusk. Darkness, 2012, acrylic on canvas, 145 x 225 cm – Photograph by Dorte Krogh – By kind permission of the Artist – mariannegroennow.com
Keywords: Europe; Middle Ages; Medieval Literature; Comparative Literature